Use of sensory analysis and social media for product development driven by consumers: a case-study for smoked bacon - Saldaña Villa, Erick Manuel (2019)
Daily food selection is made without much effort and is determined by experienced, affective, and intuitive processes, commonly expressed through social media. However, the majority of the current studies in sensory and consumer science use classical methods without considering social media, which are currently used to express the \"consumer-voice\". This fact could jeopardize the ecological validity and reliability of the current sensory methods. In this sense, studies based on classical and new sensory methods, along with social media, could provide more realistic results, since social desirable and rationalized responses to a \"stimulus\" would be prevented. In this context, the objective of the current work was to study the transition from classical sensory analysis to social media as an alternative in the development of smoked bacon considering the consumer\'s response. This thesis is divided into eight studies, with the first four studies based on the intrinsic properties of the product. In the following two studies the dynamic sensory perception, using the Temporal Dominance of Sensations, was studied. The two final studies addressed the non-sensory properties associated with smoked bacon. The results of the present study indicated that the static sensory properties and the volatile profile of bacon were dependent on the smoking process. The dynamic sensory properties were dependent on the smoking, fat content and mastication. Non-sensory factors affected the representation of smoked bacon, with healthiness being the most important factor, followed by context of consumption and convenience. The lexicometric analysis of the tweets revealed that the main associations of the word bacon in twitter were: culinary preparations, occasions of consumption and positive feelings. Finally, it can be concluded that the transition process from classical methods to social networks is a growing phenomenon, which seeks to complement the static and dynamic intrinsic sensory measurements in the search for a better understanding of consumer\'s behavior.